CROSS-DISCIPLINARY CARE PATHWAYS: SYNERGIES BETWEEN MEDICAL SECRETARY, RADIOLOGY, PHARMACY, AND EMERGENCY PRACTICES IN NURSING-ENHANCED ENVIRONMENTS - Mubarak Alhemidi Alshammari, Meshal Khalaf Al Dhafeeri, Munirah Tamash Khabur Al Dhafeeri, Abdulmajeed Hamdan Alshammari, Faisal Hamdan Alshammari, Hamdah Sowied Noman Al Dhafeeri, Ghazwah Saket Al Dhafeeri, Samar Suwayyid Jarad Alanzi, ,; Abdulrahman Huzaym Hamed Al Anazi, Fawaz Majed Ali Almutairi, Fatimah Abdullah Alrasheedi, Khaled Safaq Al-Harbi, Ahmed Nasser Al-Mutairi, Abdulkarim Ayed Hmdan, Abdulrahman Huzaym Hamed Alanazi, Ghazwah Saket Aldhafeeri, Hamda Sawayed Aldhofeery,; Hakim Haif K Al Dhafeeri, (Chelonian Research Foundation, 2022)
The increasing complexity of healthcare and the need for efficient, patient-centered care have led to the development of cross-disciplinary care pathways. This study aims to explore the synergies between medical secretary, radiology, pharmacy, and emergency practices in nursing-enhanced environments and their impact on patient outcomes. A mixed-methods approach was employed, combining a systematic literature review, surveys, and focus group discussions with healthcare professionals from the targeted disciplines. The findings suggest that effective collaboration and communication among medical secretary, radiology, pharmacy, and emergency teams, coupled with nursing-enhanced environments, lead to improved diagnostic accuracy, medication safety, and timely interventions. Key facilitators of successful cross-disciplinary care pathways include shared decision-making, standardized protocols, and interprofessional education. Barriers identified include limited resources, divergent professional cultures, and communication breakdowns. The study concludes that fostering synergies between medical secretary, radiology, pharmacy, and emergency practices in nursing-enhanced environments can significantly improve patient outcomes, reduce healthcare costs, and enhance the quality of care. Recommendations for practice and future research are provided.